Summary of Consensus Report on Preoperative Evaluation - Ozkan, Metin; Kirkil, Gamze; Dilektasli, Asli Gorek; Sogut, Ayhan; Sertogullarindan, Bunyamin; Cetinkaya, Erdogan; Kovan, Tezay (Bilimsel Tip Publishing House, 2015)
[Abstract Not Available]
Keywords: Postoperative Pulmonary Complications; College-of-Physicians; Duchenne Muscular-Dystrophy; Obstructive Lung-Disease; Abdominal-Surgery; Noncardiothoracic Surgery; Respiratory Complications; Multivariate-Analysis; Tracheal Intubation; Smoking-Cessation